MANAGEMENT SYSTEM OF EDUCATIONAL ESTABLISHMENTS IN THE SPHERE OF TOURISM AND HOSPITALITY IN SWITZERLAND - Наталія Закордонець (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The essence of the management system of educational establishments in the sphere of tourism and hospitality in Switzerland has been reviewed. It has been noted that the organization of the educational process in educational institutions of the country is determined by the decentralized and federalist structure of the Swiss education system. Management policies at different hierarchical levels have been considered: federal, cantonal and communal. It has been found that the accreditation system of tourism education in Switzerland holds a special significance, since replacing the system of federal control. Much attention has been paid to the Swiss Hotel Schools Association and its role in politics of increasing excellence in tourism education. It has been noted that the modernization of the Swiss system of training of future specialists in tourism is being made by decentralization of education management in tourism and the usage of international accreditation as a means of measuring the quality of tourism education. Examples of the applying of exceptional management practices of Swiss tourism and hospitality management programs in higher education institutions of Ukraine have been verified.